Iguratimod Alleviates Myocardial Ischemia/Reperfusion Injury Through Inhibiting Inflammatory Response Induced by Cardiac Fibroblast Pyroptosis via COX2/NLRP3 Signaling Pathway - Zhang, Mian; Lei, Yi-shan; Meng, Xiao-wen; Liu, Hua-yue; Li, Lin-gui; Zhang, Jun; Zhang, Jia-xin; Tao, Wen-hui; Peng, Ke; Lin, Jun; Ji, Fu-hai (Frontiers in Cell and Developmental Biology, 2021)
Background: NLRP3 inflammasome contributes a lot to sterile inflammatory response and pyroptosis in ischemia/reperfusion (I/R) injury. Cardiac fibroblasts (CFs) are regarded as semi-professional inflammatory cells and they exert immunomodulatory role in heart. Iguratimod provides protective role in several human diseases through exerting powerful anti-inflammatory effect. However, it is still unclear whether Iguratimod can alleviate myocardial I/R injury and whether inflammation triggered by NLRP3-related pyroptosis of CFs is involved in this process. Methods: Transcriptomics analysis for GSE160516 dataset was conducted to explore the biological function of differentially expressed genes during myocardial I/R. In vivo, mice underwent ligation of left anterior descending coronary artery for 30 min followed by 24 h reperfusion. In vitro, primary CFs were subjected to hypoxia for 1 h followed by reoxygenation for 3 h (H/R). Iguratimod was used prior to I/R or H/R. Myocardial infarct area, serum level of cardiac troponin I (cTnI), pathology of myocardial tissue, cell viability, lactate dehydrogenase (LDH) release and the expression levels of mRNA and protein for pyroptosis-related molecules were measured. Immunofluorescence was applied to determine the cellular localization of NLRP3 protein in cardiac tissue. Results: During myocardial I/R, inflammatory response was found to be the most significantly enriched biological process and NOD-like receptor signaling was a crucial pathway in mediating cardiac inflammation. In our experiments, pretreatment with Iguratimod significantly ameliorated I/R-induced myocardial injury and H/R-induced pyroptosis of CFs, as evidenced by reduced myocardial infarct area, serum cTnI level and LDH release in supernatants, as well as improved pathology of cardiac tissue and cell viability. Immunofluorescence analysis showed that NLRP3 was mainly localized in CFs. Moreover, Iguratimod inhibited the expression of pro-inflammatory cytokines and pyroptosis-related molecules, including NLRP3, Cleaved Caspase-1 and GSDMD-N. Conclusion: Our results suggested that inflammatory response mediated by NOD-like receptor signaling is of vital importance in myocardial I/R injury. Iguratimod protected cardiomyocytes through reducing cascade of inflammation in heart by inhibiting cardiac fibroblasts pyroptosis via COX2/NLRP3 signaling pathway.